Effect of patient‐centred self‐management programme on mental health, self‐efficacy and self‐management of patients with hypertensive nephropathy: A randomised controlled trial. Issue 21 (3rd May 2021) - Lee, Mei‐Chen; Wu, Shu‐Fang Vivienne; Lu, Kuo‐Cheng; Wang, Wen‐Hug; Chen, Yen‐Yen; Chen, Hui‐Mei
Abstract: Aim and objectives: To evaluate the effect of patient‐centred self‐management programme on mental health, self‐efficacy and self‐management of patients with hypertensive nephropathy. Background: If the symptoms of hypertension are not well‐controlled, deterioration of renal function will accelerate and evolve into hypertensive nephropathy. Design: A randomised single‐blind trial. This article follows the requirements of CONSORT statement. Methods: The experimental group ( n = 35) after pre‐test used patient‐centred self‐management programme once a week for a total of 4 weeks and the intervention effect was measured after 3 months for post‐test. Contrarily, the traditional care was employed for the control group ( n = 35). The measuring outcomes included mental health, self‐efficacy and self‐management. Trial registry is listed under https://clinicaltrials.gov/ with Identifier No. NCT04633993. Results: After the intervention, the average score of mental health for the experimental group was 20.79 ( SD = 0.82) which was higher than the 19.27 points for the control group ( SD = 0.77) and showed a significant difference ( F = 8.31, p = .005, partial eta 2 = 0.133). In terms of self‐efficacy, the average score for the experimental group was 214.13 ( SD = 6.40), which was higher than the 189.58 points for the control group ( SD = 6.03) and exhibited a significant difference ( F = 11.82, p = .001, partial eta 2 = 0.197). Regarding self‐management, the average score of the experimental group was 75.12 ( SD = 2.29) which was significantly higher than the 68.80 points of the control group ( SD = 2.43) ( F = 11.17, p = .001, partial eta 2 = 0.190). Conclusions: In addition to promoting mental health of individual cases, this intervention also increases their self‐confidence in disease control and improves their self‐management on diseases. Relevance to clinical practice: The intervention provides an effective option for clinical care workers as a replacement for or supplement to the traditional care.